IDENTIFIKASI KOMPETENSI AHLI MUDA PEMELIHARAAN JALAN DAN JEMBATAN GUNA MEMINIMALISIR KERUSAKAN: SEBUAH KAJIAN LITERATUR - Rizlinia, Affa; Eka Murtinugraha, R.; Hadi, Winoto (Lafadz Jaya Publisher, 2024)
Road and bridge infrastructure play a crucial role in Indonesia's economic growth. However, road and bridge damages frequently occur due to imbalanced growth, insufficient maintenance funding, and poorly executed maintenance practices. These conditions lead to accidents, discomfort, and hindered economic progress, underscoring the necessity for competent road and bridge maintenance experts. To become a proficient road and bridge maintenance expert, one can start at the junior level with educational requirements of a bachelor's degree in civil engineering or building technology. This study aims to identify the competencies needed to become a junior road and bridge maintenance expert. The research methodology employs a literature review approach, utilizing content analysis techniques based on sources such as SKKNI No. 112 of 2015 and relevant journals. The findings of this identification process reveal 23 competencies grouped into three aspects: knowledge, skills, and attitudes.